The Role of Providence in the Social Order : An Essay in Intellectual History - Viner, Jacob (Book collections on Project MUSE., 1976)
The essays in this book were originally presented by Professor Viner as the 1966 Jayne Lectures of the American Philosophical Society. The relationship between religious doctrines and economic theory and behavior had long interested Professor Viner, and the conclusions he discussed represented years of thoughtful study. They focus in particular on the way in which providence was used to justify existing economic and social conditions. The author points out that providence favors trade among peoples in order to promote universal brotherhood; providence also creates social inequality because i.